2011
DOI: 10.1111/j.1463-1318.2011.02679.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal risks of sodium phosphate tablets for colonoscopy preparation: a review of adverse drug reactions reported to the US Food and Drug Administration

Abstract: Renal adverse drug reactions from sodium phosphate tablets are more common in women with a mean body weight lower than the national average weight.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 28 publications
1
17
0
1
Order By: Relevance
“…After being infected with MTB, the body weight of mice decreased while Kw/Bw increased. This was in consistence with former studies, where a reduction in body weight was followed by an elevation of Kw/Bw in mice with renal injury [26,27]. MTB-infected mice showed increased levels of BUN and Scr, which indicated that renal injury is characterized by higher levels of BUN and Scr.…”
Section: Discussionsupporting
confidence: 89%
“…After being infected with MTB, the body weight of mice decreased while Kw/Bw increased. This was in consistence with former studies, where a reduction in body weight was followed by an elevation of Kw/Bw in mice with renal injury [26,27]. MTB-infected mice showed increased levels of BUN and Scr, which indicated that renal injury is characterized by higher levels of BUN and Scr.…”
Section: Discussionsupporting
confidence: 89%
“…A possible explanation for the asymmetric sex distribution is that women have lower BMIs than do men, but the OSP dose is usually the same [61,104]. However, dosage alone is not completely responsible for this phenomenon.…”
Section: Age Gender and Body Constitutionmentioning
confidence: 84%
“…According to other studies, females and/or smaller and leaner subjects, of both sexes, were at greater risk for developing AKI after OSP than average males [32,[102][103][104].…”
Section: Age Gender and Body Constitutionmentioning
confidence: 98%
“…El estudio retrospectivo de la doctora Ehrenpreis y colaboradores, realizado a partir de la base de datos de eventos adversos de la Food and Drug Administration (FDA), desde 2004 hasta 2009, demostró que la tableta de fosfato de sodio se asocia a eventos de lesión renal, más frecuentemente en mujeres con un promedio de peso más bajo de lo normal (68.57 ± 1.78 kg) 6 .…”
Section: Ce Dfunclassified